A comparative study of myocardial molecular phenotypes of two tfr2β null mice: Role in ischemia/reperfusion. (13th October 2015) - Boero, Martina; Pagliaro, Pasquale; Tullio, Francesca; Pellegrino, Rosa M.; Palmieri, Antonietta; Ferbo, Ludovica; Saglio, Giuseppe; De Gobbi, Marco; Penna, Claudia; Roetto, Antonella
Abstract Transferrin receptor 2 (Tfr2) is an iron‐modulator transcribed in two isoforms, Tfr2α and Tfr2β. The latter is expressed in the heart. We obtained two mouse models with silencing of Tfr2β: one with a normal systemic iron amount (SIA), i.e., Tfr2‐KI, and the other, i.e., LCKO‐KI, with high SIA due to hepatic Tfr2α silencing. We aimed to assess whether Tfr2β might play a role in myocardial injury and whether Tfr2β silencing might modify proteins of iron metabolism, antioxidant, apoptotic, and survival enzyme activities in the heart undergoing ischemia/reperfusion (I/R). Isolated hearts of wild‐type (WT) and Tfr2‐null mice were studied before or after an I/R protocol, and proteins/RNA analyzed by Western blot and/or quantitative PCR. Tfr2β increased in WT hearts subject to I/R, and both Tfr2β null mice hearts were protected against I/R injury (about 40% smaller infarct‐size compared to WT hearts). RISK kinases (ERK1/2‐AKT‐PKCε) were found up‐regulated after I/R in Tfr2‐KI, whereas SAFE enzyme (Stat3) and GSK3β resulted phosphorylated during I/R in LCKO‐KI hearts. While HO‐1 and HIF‐2a were high in both Tfr2β‐null mice, Catalase, and proapoptotic factors were upregulated only in LCKO‐KI. Finally, Tfr2‐KI hearts presented an increased Ferritin‐H and a decreased Ferroportin1, whereas LCKO‐KI hearts displayed an upregulation of Ferritin‐L chain and DMT1/Hamp‐RNA. In conclusion, Tfr2β isoform is involved in cardiac iron metabolism and its silencing leads to a protected phenotype (antioxidants, RISK, and/or SAFE upregulation) against I/R challenging. Iron‐dependent signals involved in cardioprotection seem to be positively affected by Tfr2β downregulation and subsequent Ferritins upregulation. © 2015 BioFactors, 41(5):360–371, 2015